2013
DOI: 10.5194/npg-20-1137-2013
|View full text |Cite
|
Sign up to set email alerts
|

Maximal Lyapunov exponent variations of volcanic tremor recorded during explosive and effusive activity at Mt Semeru volcano, Indonesia

Abstract: Abstract. We analyze 25 episodes of volcanic tremor recorded from 22 November until 31 December 2009 at Mt Semeru volcano in order to investigate their spectral and dynamical properties. The overtone frequencies for most of the tremor events indicate a pattern of period-doubling, which is one possible route that can lead a system to chaotic behavior. Exponential divergence of the phase space orbits is a strong indicator of chaos and was quantified by estimating the maximal Lyapunov exponent (MLE) for all tremo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
6
0
1

Year Published

2016
2016
2023
2023

Publication Types

Select...
8
1
1

Relationship

0
10

Authors

Journals

citations
Cited by 13 publications
(7 citation statements)
references
References 30 publications
(39 reference statements)
0
6
0
1
Order By: Relevance
“…For each 20-min segment, the permutation entropy for the vertical component, filtered in the frequency range 0.5-10 Hz, was calculated. The use of this parameter to detect volcanic tremor is supported by numerous studies that associate its source mechanism to a lowdimensional nature (e.g., Konstantinou et al 2013). The dimension of a time series is a measure of its complexity, which is generally extracted in the reconstructed phase space by computing the fractal dimension, Lyapunov exponents, or Kolmogorov-Sinai entropy, among others (see Abarbanel et al 1993, for a review).…”
Section: Permutation Entropymentioning
confidence: 99%
“…For each 20-min segment, the permutation entropy for the vertical component, filtered in the frequency range 0.5-10 Hz, was calculated. The use of this parameter to detect volcanic tremor is supported by numerous studies that associate its source mechanism to a lowdimensional nature (e.g., Konstantinou et al 2013). The dimension of a time series is a measure of its complexity, which is generally extracted in the reconstructed phase space by computing the fractal dimension, Lyapunov exponents, or Kolmogorov-Sinai entropy, among others (see Abarbanel et al 1993, for a review).…”
Section: Permutation Entropymentioning
confidence: 99%
“…The type of eruption of the Semeru is Strombolian, because it involves the fragmentation of low viscosity basaltic magma by volatile degassing [9]. Other volcanological studies have suggested that the Semeru eruption type is vulcanian with VEI ranging between 2 and 3, because it has generated eruption columns, lava dome growth, and small pyroclastic flow [11], has produced basaltic incandescent lavas; and was accompanied by hot clouds. The greatest eruption occurred in 1944.…”
Section: The Profile Of Characteristic Volcanic Eruption In Indonesiamentioning
confidence: 99%
“…Penentuan dimensi fraktal merupakan analisis non linier untuk mengidentifikasi dinamika dari sumber tremor vulkanik suatu gunungapi bersifat kaotik atau tidak (Konstantinou et al, 2013). Beberapa penelitian mengenai analisis fraktal yang sudah dilakukan di beberapa gunungapi antara lain analisis fraktal tremor vulkanik yang terekam di gunung Semeru (Maryanto & Mulyana, 2008) (Konstantinou et al, 2013) dan analisis fraktal tremor vulkanik yang terekam di gunung Sakurajima (Maryanto, Santosa, Mulyana, & Hendrasto, 2011 ( 1) dimana px(i) merupakan probability distribution dari Xi dan py(j) merupakan probability distribution dari Yj (j=α,α+1,…, α+M) . Gambar 1 merupakan delay time tremor vulkanik gunung Raung didapatkan 0,08 sekon (timelag dikalikan dengan sampling rate) (Fraser & Swinney, 1986).…”
Section: Gunungapiunclassified